2020
DOI: 10.1186/s13006-020-00281-0
|View full text |Cite
|
Sign up to set email alerts
|

Helpful and challenging aspects of breastfeeding in public for women living in Australia, Ireland and Sweden: a cross-sectional study

Abstract: Background Breastfeeding in public continues to be contentious with qualitative evidence confirming that women face many challenges. It is therefore important to gain understanding of not only the challenges but also what women perceive is helpful to breastfeed in public. Methods A cross-sectional study was conducted with women living in Australia, Ireland or Sweden currently breastfeeding or having breastfed within the previous 2 years. Our object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…There are large inequalities in infant feeding experience along structural lines in the UK and similar HIC (Victora et al, 2016), contributing to socioeconomic gradients in inflammation and infant weight (McDade & Koning, 2021). These inequalities exist due to cultural and religious norms around breastfeeding, particularly in public (Chang et al, 2021), access to social support (Grubesic & Durbin, 2020;Tomori, 2009), opportunity costs of breastfeeding (Hough et al, 2018;Tully & Ball, 2018), as well having convenient and quickto-access places to breastfeed (Brown et al, 2020;Hauck et al, 2020). Furthermore, the experience of breastfeeding problems is unlikely to be evenly distributed as one study found that young, unmarried and non-college educated US women were more likely to experience breastfeeding problems resulting in disrupted lactation (Stuebe et al, 2014).…”
Section: Hypothesis 3: the Type Of Support Impacts The Moderating Effectmentioning
confidence: 99%
“…There are large inequalities in infant feeding experience along structural lines in the UK and similar HIC (Victora et al, 2016), contributing to socioeconomic gradients in inflammation and infant weight (McDade & Koning, 2021). These inequalities exist due to cultural and religious norms around breastfeeding, particularly in public (Chang et al, 2021), access to social support (Grubesic & Durbin, 2020;Tomori, 2009), opportunity costs of breastfeeding (Hough et al, 2018;Tully & Ball, 2018), as well having convenient and quickto-access places to breastfeed (Brown et al, 2020;Hauck et al, 2020). Furthermore, the experience of breastfeeding problems is unlikely to be evenly distributed as one study found that young, unmarried and non-college educated US women were more likely to experience breastfeeding problems resulting in disrupted lactation (Stuebe et al, 2014).…”
Section: Hypothesis 3: the Type Of Support Impacts The Moderating Effectmentioning
confidence: 99%
“…There are large inequalities in infant feeding experience along structural lines in the UK and similar HIC (Victora et al, 2016), contributing to socioeconomic gradients in inflammation and infant weight (McDade & Koning, 2021). These inequalities exist due to cultural and religious norms around breastfeeding, particularly in public (Chang et al, 2021), access to social support (Grubesic & Durbin, 2020; Tomori, 2009), opportunity costs of breastfeeding (Hough et al, 2018; Tully & Ball, 2018), as well having convenient and quick‐to‐access places to breastfeed (Brown et al, 2020; Hauck et al, 2020). Furthermore, the experience of breastfeeding problems is unlikely to be evenly distributed as one study found that young, unmarried and non‐college educated US women were more likely to experience breastfeeding problems resulting in disrupted lactation (Stuebe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, some partners (Alianmoghaddam et al, 2017;Hauck et al, 2020;Leeming et al, 2013;Majee et al, 2017;Owens et al, 2018;Pallotti, 2016;Shortt et al, 2013;Swigart et al, 2017), family members (Alianmoghaddam et al, 2017;Hauck et al, 2020;Majee et al, 2017;Schafer et al, 2019;Sheehan et al, 2019), and friends (Alianmoghaddam et al, 2017;Chopel et al, 2019;DeMaria et al, 2020;Hauck et al, 2020;Schafer et al, 2019) were supportive of breastfeeding in public. Staff working in public places both encouraged (Hauck et al, 2020;Mathews, 2018;Schmied et al, 2019) and discouraged (Chopel et al, 2019;Mathews, 2018;McKenzie et al, 2018) breastfeeding in public.…”
Section: Social Environment: Peoplementioning
confidence: 99%
“…Negative beliefs associated with breastfeeding in public translated into individual mothers being discouraged from breastfeeding in public by partners (Dayton et al, 2019;Isherwood et al, 2019;Sheehan et al, 2019;Stav, 2019) and family (Isherwood et al, 2019;Newman & Williamson, 2018;Prendergast & James, 2016;Sheehan et al, 2019;Stav, 2019). Contrastingly, some partners (Alianmoghaddam et al, 2017;Hauck et al, 2020;Leeming et al, 2013;Majee et al, 2017;Owens et al, 2018;Pallotti, 2016;Shortt et al, 2013;Swigart et al, 2017), family members (Alianmoghaddam et al, 2017;Hauck et al, 2020;Majee et al, 2017;Schafer et al, 2019;Sheehan et al, 2019), and friends (Alianmoghaddam et al, 2017;Chopel et al, 2019;DeMaria et al, 2020;Hauck et al, 2020;Schafer et al, 2019) were supportive of breastfeeding in public. Staff working in public places both encouraged (Hauck et al, 2020;Mathews, 2018;Schmied et al, 2019) and discouraged (Chopel et al, 2019;Mathews, 2018;McKenzie et al, 2018) breastfeeding in public.…”
Section: Social Environment: Peoplementioning
confidence: 99%
See 1 more Smart Citation